Trauma-sensitive school concepts for students with a refugee background: a review of international studies - Lembke, Eva J.; Linderkamp, Friedrich; Casale, Gino (Frontiers in Psychology, 2024)
Children and adolescents with a refugee background are at high risk for traumatization. Once they arrive in safe countries, schools are the institutions where teachers are responsible for caring for them sensitively and competently. Furthermore, schools are organized in learning groups consisting of multiple peers of the same age, which provides excellent opportunities for social learning and experiences of social support. In this respect, schools are the appropriate places where preventive concepts can be applied to students with a refugee background. This systematic review summarizes studies that examine or evaluate existing international concepts of trauma-sensitive schools for supporting traumatized students with a refugee background. Based on N = 41 selected articles, 17 relevant concepts of trauma-sensitive schools were identified. In 35.3% of the concepts, traumatized students with a refugee background are explicitly included in the target group of the concept, while 47.1% of the concepts refer to groups of students with trauma as a result of various adverse childhood experiences, which also occur more frequently within the population of refugee children and adolescents 17.6% of the concepts contain specific adaptations for pupils with a refugee background. The majority of these concepts were developed in the United States. Additional concepts can be reported for Australia, the United Kingdom, Turkey, and Cambodia. Based on available empirical data, no significant effectiveness regarding the researched concepts’ effects on academic and other school-related data can be determined. Although some studies indicate positive effects concerning school-related target variables, most of the studies have only limited significance due to inadequate research designs and methodological deficiencies. Therefore, there is a great need for further development, careful implementation, and evaluation of trauma-sensitive concepts in schools, especially for the growing group of refugee students.